Research progress on the mechanism of exosome-mediated virus infection - Zhang, Hanjia; Liu, Xuanyi; Shi, Jiuming; Su, Xuan; Xie, Jiayuan; Meng, Qingfeng; Dong, Hao (Frontiers in Cellular and Infection Microbiology, 2024)
Exosomes are extracelluar vesicles that facilitate intercellular communication and are pivotal in post-transcriptional regulation within cellular gene regulatory networks, impacting pathogen dynamics. These vesicles serve as crucial regulators of immune responses, mediating cellular interactions and enabling the introduction of viral pathogenic regions into host cells. Exosomes released from virus-infected cells harbor diverse microRNAs (miRNAs), which can be transferred to recipient cells, thereby modulating virus infection. This transfer is a critical element in the molecular interplay mediated by exosomes. Additionally, the endosomal sorting complex required for transport (ESCRT) within exosomes plays a vital role in virus infection, with ESCRT components binding to viral proteins to facilitate virus budding. This review elucidates the roles of exosomes and their constituents in the invasion of host cells by viruses, aiming to shed new light on the regulation of viral transmission via exosomes.